A new hardware-assisted PIR with O(n) shuffle cost - DING, Xuhua (Institutional Knowledge at Singapore Management University, 2010)
Since the concept of private information retrieval (PIR) was first formalized by Chor et al., various constructions have been proposed with a common goal of reducing communication complexity. Unfortunately, none of them is suitable for practical settings mainly due to the prohibitively high cost for either communications or computations. The booming of the Internet and its applications, especially, the recent trend in outsourcing databases, fuels the research on practical PIR schemes. In this paper, we propose a hardware-assisted PIR scheme with a novel shuffle algorithm. Our PIR construction entails O(n) offline computation cost, and constant online operations and O(log n) communication cost, where n is the database size.